Khaled Aboe el-Fadl: Against Authoritarianism Teachers Talk to God - Parjiman Lathif (Universitas Ahmad Dahlan, 2019)
A similar Qur’anic text with Allah Almighty as its creator is often interpreted differently among Muslims. In the process of interpretation of religious texts, the three elements, i.e., reader, text, and author are interrelated. Separating the three of them can give rise to otriarianism in interpreting the meaning of the text, which is considered an act of arbitrariness so that it is not uncommon for someone to assume the most correct interpretation. To avoid this attitude, according to Khaled Abou El Fadl, a negotiating process should be built between the three so that each does not dominate in the process of determining the meaning of the text. This paper is intended to describe the best relationship between the reader, the text and the word of Allah in the theory of the negotiation of Khaled Abou El Fadl.